Tomographic determination of residual ridges shape and size prevalence in edentate patients - Varón-de Gaitán, Amparo Constanza; Bustamante-Mesa, Juan Carlos; Hoyos-Galvis, Ana Catalina; Zapata-Suárez, Andrés Felipe; Plaza-Ruíz, Sonia Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: the objective of this tomographic study was to determine residual ridges shape and size prevalence in edentate patients and its association with age, sex, and upper and lower residual ridge. Methods: we evaluated 722 scans taken at the UniCIEO diagnostic center between 2010 and 2012, obtaining 102 residual ridges images, 70 of the maxilla and 32 of the mandible, from 73 patients (46 women and 27 men) aged between 24.67 and 90.17 years. The evaluation of residual ridge size and shape was achieved through nine templates generated by the Galaxis 3D computer program, of the Cone beam GALILEOS system (Sirona Dental Systems Inc., Bensheim, Germany). Results: the prevalent shape and size of upper residual ridge were: large ovoid 48.6%, large triangular 42.9%, medium triangular 4.3%, large square 2.9%, medium ovoid 1.4%; and in the mandible they were: large ovoid 93.8%, and large square 6.25%. Conclusions: the most prevalent residual ridge size and shape was large ovoid both in the upper and lower maxilla. We found no association between shape/size and any of the variables under study.